LINEAR DIFFERENTIAL SYSTEM OF THE FIRST ORDER AND THE NEW METHOD FOR DETERMINED THE FUNDAMENTAL MATRIX - MACURA, Dusan (Trends in education, 2010)
The method of the auxiliary numbers of the theory linear differential systems of the first - order with the constant coefficients is apply on the linear differential system of the first order with using the sequences matrix.
Keywords: differential system; sequence matrix.